Hubungan Pola Pengasuhan Terhadap Kejadian Stunting Pada Balita Umur 6-59 Bulan Di Kelurahan Mangasa (Window of Public Health Journal, 2025)
Stunting, a nutritional issue in toddlers that has not been adequately addressed, is the focus of this study. A person is considered stunted if their Height-for-Age (H/U) Z-score is below -2SD (standard deviation). In accordance with the Sustainable Development Goals (SDGs), it is hoped that by 2030, all types of malnutrition will be overcome, including reducing stunting and wasting rates in toddlers, in line with the global targets set until 2025. The World Health Organization (WHO) estimates that the prevalence of stunting worldwide reached 22% in 2020, affecting approximately 149.2 million toddlers. This study, which employed a quantitative method with a cross-sectional study design, focused on 68 toddlers, of whom 47 were identified as stunted. Data were collected through questionnaires and analyzed using the chi-square test to evaluate the relationship between existing variables. The research findings show that there is no significant relationship between dietary patterns and the incidence of stunting (p = 0.526) in toddlers aged 6-59 months in Mangasa Village, Makassar City. Similarly, there was no relationship between exclusive breastfeeding and the incidence of stunting (p = 0.676) in toddlers of the same age range in Mangasa Village, Makassar City. Likewise, there is no relationship between maternal support in health service practices and the incidence of stunting (p = 0.630) in toddlers aged 6-59 months in Mangasa Village, Makassar City. This study revealed that among dietary patterns, exclusive breastfeeding, and maternal support in health services, there is no significant relationship related to stunting in children aged 6 to 59 months in Mangasa Village. These findings have the potential to shape future policies and interventions. The community is encouraged to continue providing exclusive breastfeeding and maintaining a balanced diet to support maternal and child health, increase family support in child care, and utilize health services such as integrated health posts (posyandu) and community health centers regularly.